EVALUASI IMPLEMENTASI PROGRAM PENANGANAN ANAK JALANAN, GELANDANGAN DAN PENGEMIS BERDASARKAN PERATURAN DAERAH KOTA MALANG NOMOR 9 TAHUN 2013 - Yakobus Margilan; Nanang Bagus (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: The country development has a negative side that always leaves the issue related to the welfare of its people. Likewise, what happens in Malang such as street children, homeless people and beggars become a problem. This study aimed to find out the evaluation of implementation of handling of street children, homeless and beggars program, the supporting factors and obstacles in Malang Social Service Agency. The type of research used qualitative method, data source using primary and secondary data. Data collection was conducted through interviews, observation and documentation. The technique of determining informants used snowball sampling. Data analysis was conducted by reduction, data presentation, and conclusions. Meanwhile the data validity used triangulation technique. The result of the evaluation of program implementation in concern with street children handling, homeless people and beggars has gone well, as seen from Smart Work Strategic Program and Service Operational Standard. Supporting factors: linearity, efficiency achieved good results, productivity is planned. As well as inhibiting factors: minimal fund linearity, human resources, not punctual. Efficiency of resource utilization has not reached target. Productivity has not reached the ability specified by the Malang Social Service Agency. Keywords: Evaluation, Implementation, Street Children, Homeless and Beggar Abstrak: Kemajuan Negara memiliki sisi negatif yang selalu menyisakan persoalan terkait kesejahteraan masyarakatnya. Demikian juga yang terjadi di Kota Malang yaitu anak jalanan, gelandangan dan pengemis menjadi persoalan. Penelitian ini bertujuan untuk mengetahui evaluasi implementasi program penanganan anak jalanan, gelandangan dan pengemis, faktor pendukung dan penghambatnya di Dinas Sosial Kota Malang. Jenis penelitian menggunakan metode kualitatif, sumber data menggunakan data primer dan sekunder. Pengumpulan data melalui wawancara, observasi dan dokumentasi. Teknik penentuan informan menggunakan snowball sampling. Analisis data dengan reduksi, penyajian data, dan kesimpulan. Keabsahan data menggunakan teknik triangulasi. Hasilnya evaluasi implementasi program penanganan anak jalanan, gelandangan dan pengemis sudah berjalan dengan baik, dilihat dari Program Kerja Rencana Strategis Smart dan Standar Operasional Pelayanan. Faktor pendukung: linearitas, efisiensi mencapai hasil baik, produktivitas direncanakan. Serta Faktor penghambat: linearitas dana minim, sumber daya manusia, tidak tepat waktu. Efisiensi pendayagunaan sumber daya belum mencapai target. Produktivitas belum mencapai kemampuan yang ditentukan Dinas Sosial Kota Malang. Kata Kunci : Evaluasi, Implementasi, Anak Jalanan, Gelandangan dan Pengemis